Peningkatan Literasi Kebencanaan Guna Membangun Kesiapsiagaan Masyarakat Menghadapi Bencana Banjir di Kelurahan Bidara Cina - Rahmat, Hayatul Khairul; Meidiyustiani, Rinny (Indonesian Journal of Emerging Trends in Community Empowerment, 2024)
Flooding is the overflowing of a river due to water exceeding the capacity of the river so that it overflows and inundates the plains or lower areas around it. DKI Jakarta Province has various complex disaster-related problems with 40% of its area being lowlands that are prone to flooding. One of these areas is Bidara Cina Village which is an area that is often affected by flooding in DKI Jakarta which is located in Jatinegara District, East Jakarta. It should be realized that efforts are needed to reduce the impact of a greater disaster by carrying out holistic and comprehensive disaster management efforts so that the risk of the disaster can be reduced so that it can build community preparedness in an area, especially in RT. 007/ RW. 001 Bidara Cina Village. Based on the above, it is important to carry out community service activities entitled "Increasing Disaster Literacy to Build Community Preparedness to Face Flood Disasters in RT. 007/ RW. 001, Bidara Cina Village, Jatinegara District, East Jakarta". The target of this community service activity is to convey knowledge about disaster literacy to build community preparedness in facing flood disasters in RT. 007/ RW. 001, Bidara Cina Village, Jatinegara District, East Jakarta and the community knows how to manage and sort waste. The community service activity that has been carried out well without significant obstacles and there is a conclusion that this community service activity has been carried out communicatively, seen from the participants who are enthusiastic in the question-and-answer process, provide responses when asked and ask questions and listen to explanations of the questions given. With this training, it is hoped that disaster literacy will increase community preparedness in facing flood disasters and waste management and sorting in RT. 007/ RW. 001, Bidara Cina Village, Jatinegara District, East Jakarta.